2013
DOI: 10.1007/s00595-013-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury following blunt abdominal trauma: a new mechanism-driven classification

Abstract: PurposesThe current classifications for blunt liver trauma focus only on the extent of liver injury. However, these scores are independent from the localization of liver injury and mechanism of trauma.MethodsThe type of liver injury after blunt abdominal trauma was newly classified as type A when it was along the falciform ligament with involvement of segments IVa/b, III, or II, and type B when there was involvement of segments V–VIII. With the use of a prospectively established database, the clinical, periope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
0
25
0
2
Order By: Relevance
“…A study carried out by Slotta et al, showed a male:female ratio of 42:22. 1 Similarly, a study carried out by Patel et al, showed a ratio of 39:3. Also, a study carried out by Mucha P et al showed a male:female ratio 163:74 i.e.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A study carried out by Slotta et al, showed a male:female ratio of 42:22. 1 Similarly, a study carried out by Patel et al, showed a ratio of 39:3. Also, a study carried out by Mucha P et al showed a male:female ratio 163:74 i.e.…”
Section: Discussionmentioning
confidence: 89%
“…after 24-48hrs) after the trauma. 1 In India, we frequently still encounter patients presenting late after abdominal injury and therefore all that is current in the literature may not be directly applicable to our situation. A better understanding of the function of spleen and its function especially in immunological defense has led to the practice of conserving Spleen in blunt abdominal injuries.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that liver injuries due to blunt force trauma are mainly associated with the right lobe (67.6%) [6] which is better tolerated than the left lobe which allows for the selection of a conservative non operative treatment approach in these patients. Slotta [7] developed a classification, based on the localization of liver injury and the mechanism of the underlying blunt liver trauma, into two types: Type A, involving the left liver lobe mostly along the falciform and Type B injury, which though considered more complex injuries than Type A, are localised to the right lobe but are associated with no increase in mortality than type A injuries.…”
Section: Classification Of Liver Injuriesmentioning
confidence: 99%
“…Liver is the most often injured organ due to abdominal trauma with its big dimension and its fixed position (1). In recent years the management of liver injury all over the world is going to include conservative management and thus aimed to avoid from any unnecessary surgery.…”
Section: To the Editormentioning
confidence: 99%